Crop diversification in Odisha: an analysis based on panel data - Chittaranjan Nayak; Chinmaya Ranjan Kumar (Agricultural Economics Research Review, 2023)
Crop diversification is considered as a pathway to promote agricultural development. The present paper examines the subtleties of crop diversification in Odisha, an eastern state in India through spatial trends across 30 districts and determinants of crop diversification. The analysis carried out from 1993-94 to 2012-13 indicates sluggishness and unevenness in crop diversification. The coastal districts lack diversification while several of the districts falling in the southern part of the state tend to be more diversified. The analysis reveals that greater use of high-yielding crop varieties and access to irrigation have influenced crop concentration, whereas rural roads and income have led to crop diversification.